Novel paradigm of therapeutic intervention for skin cancer: challenges and opportunities - Modassir Nasim; Mariya Khan; Rabea Parveen; Azka Gull; Saba Khan; Javed Ali (SpringerOpen, 2024)
Abstract Background Skin cancer continues to be an imperative global health issue, urging continuous exploration of treatment methodologies. Conventional treatments for skin cancer include surgical interventions, immunotherapy, targeted therapy, chemotherapy, and radiation therapy. However, these methods often present obstacles like treatment resistance, systemic toxicity, limited effectiveness in advanced stages, infection risk, pain, long recovery, and impact on healthy tissue. Main body of the abstract Nanomedicine holds promise by facilitating precise drug administration, early detection, and heightened therapeutic efficiency via targeted and localized delivery systems. The integration of nanomedicine into skin cancer alleviation therapies demonstrates optimistic outcomes, including refined drug delivery, augmented bioavailability, minimized adverse effects, and potential theranostic applications. Recent breakthroughs in nanomedicine have propelled advancements in skin cancer treatment, showing significant potential in transforming the treatment paradigm. The presents review provides comprehensive aspects of existing skin cancer treatments and their challenges, spotlighting recent breakthroughs propelled by nanomedicine. Short conclusion This abstract delineates the present landscape of skin cancer treatments, underscores their constraints, and highlights recent strides in nanomedicine that have the potential to transform the paradigm of skin cancer treatment, ultimately elevating patient prognosis. Importantly, the present review emphasizes substantial challenges that hinder the clinical translation of nanomedicines and suggests possible remedies to surpass them. Graphic abstract